(untitled) (Research, Society and Development, 2021)
Objective: To analyze, through a review of the literature, the implication of the new coronavirus in breastfeeding in times of pandemic. Materials and Methods: Integrative review in three databases: SciELO; BVS and Academic Google, in Portuguese, English and Spanish, using indexed words from the following descriptors in Science and Health (DECs): SARS-CoV-2, Covid-19, Breastfeeding and Nursing Care. Totaling 30 studies (27 articles and 3 references from government agencies). Results: Breastfeeding brings many health benefits to children and their mothers. Breastfeeding is the cornerstone of infant and young child survival, nutrition and development, and maternal health. Currently, the possible transmission of the virus through breastfeeding is still under debate. Recommendations on mother-infant contact and breastfeeding should be based on a thorough consideration not only of the potential risks of infection of the baby with Covid-19, but also of the morbidity and mortality risks associated with non-breastfeeding, the inappropriate use of formulas. infant milks, as well as the protective effects of skin-to-skin contact. Conclusion: Based on current evidence, transmission of the virus through breast milk has not been found to date. For this reason, the benefits of breast milk outweigh the risk of interruption of breastfeeding and potential transmission of the coronavirus.